A narrative literature review of older people's cancer pain experience. Issue 15 (29th March 2013) - Dunham, Margaret; Ingleton, Christine; Ryan, Tony; Gott, Merryn
<x xml:space="preserve">Abstract</x> Aims and objectives To synthesise current evidence about the experience of older people with cancer pain and consider how exploration of this may inform clinical practice and research. Background Cancer is more prevalent in older age. Evidence suggests that older people's pain is generally under‐recognised and under treated. Pain is a significant concern for many people living and dying with cancer and may be of particular concern for older people who may have complex biopsychosocial needs. There is mounting evidence that older people and their families experience high level of unmet need generally and suboptimal pain in particular. Design Narrative literature review. Method A comprehensive search of five electronic databases was undertaken between the years 1996–2010 inclusive. Inclusion criteria were primary research papers relating older peoples' experiences of cancer pain, incorporating the verbal report or narrative account of experience of cancer. Results Seventeen papers met the criteria for inclusion in the review. Three major themes emerged from the literature: (1) emotional experience identified by older people with cancer pain, (2) effects of pain on life and living, and (3) how communication affects the experience or expression of cancer pain including subthemes of validating, trust and cultural effects on the communication of pain. Conclusion There is limited research about older people's cancer pain from the perspective of the person experiencing the pain. This review highlights the need for further research into living and dying with cancer pain which incorporates the unique and individual experience of older people. Relevance to clinical practice Understanding the complexity and nature of older people's cancer pain experience should inform appropriate effective care that improves quality of life and promotes independence and dignity. Culturally sensitive training in communication may enhance understanding of the needs of older people with cancer pain.